2005
DOI: 10.2298/zmspn0519161m
|View full text |Cite
|
Sign up to set email alerts
|

Lignicolous macrofungi of the Bardaca foodplain region

Abstract: In the frame of biodiversity investigation of the Bardaca floodplain (Republic of Srpska, Bosnia), the investigation of the presence and the diversity of macrofungi of the wider Bardaca region have been undertaken. The relative poor generic diversity of lignicolous macrofungi with only 21 species (11 families) representing this group has been recorded. Such a poor qualitative and also quantitative composition of this very important fungal group could be explained by heavy devastation of autochthonous plant com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Research on the diversity of lignicolous macrofungi conducted by Matavulj et al [21] indicates that 21 species of these group are present in the wider area of Bardača (today within the Ramsar site "Bardača Wetland"), while lichenological research indicated presence of 15 species of lichens in the same area [22]. Authors believe that such a rather low diversity of these two groups of organisms is associated with air pollution in some parts of the analyzed area and degradation of autochthonous plant communities by anthropogenic impact.…”
Section: Main Characteristics Of Plant and Animal Communities Of "Bardača Wetland"mentioning
confidence: 99%
“…Research on the diversity of lignicolous macrofungi conducted by Matavulj et al [21] indicates that 21 species of these group are present in the wider area of Bardača (today within the Ramsar site "Bardača Wetland"), while lichenological research indicated presence of 15 species of lichens in the same area [22]. Authors believe that such a rather low diversity of these two groups of organisms is associated with air pollution in some parts of the analyzed area and degradation of autochthonous plant communities by anthropogenic impact.…”
Section: Main Characteristics Of Plant and Animal Communities Of "Bardača Wetland"mentioning
confidence: 99%